Is impaired energy production a novel insight into the pathogenesis of pyridoxine-dependent epilepsy due to biallelic variants in ALDH7A1? - Anastasia Minenkova (Public Library of Science (PLoS), 2021)
Background Pyridoxine-dependent epilepsy (PDE) is due to biallelic variants in ALDH7A1 (PDE-ALDH7A1). ALDH7A1 encodes α-aminoadipic semialdehyde dehydrogenase in lysine catabolism. We investigated the gamma aminobutyric acid (GABA) metabolism and energy production pathways in human PDE-ALDH7A1 and its knock-out aldh7a1 zebrafish model. Methods We measured GABA pathway, and tricarboxylic acid cycle metabolites and electron transport chain activities in patients with PDE-ALDH7A1 and in knock-out aldh7a1 zebrafish. Results We report results of three patients with PDE-ALDH7A1: low paired complex I+II and complex II+III and individual complex IV activities in muscle biopsy in patient 1 (likely more severe phenotype); significantly elevated CSF glutamate in the GABA pathway and elevated CSF citrate, succinate, isocitrate and α-ketoglutarate in the TCA cycle in patient 3 (likely more severe phenotype); and normal CSF GABA pathway and TCA cycle metabolites on long-term pyridoxine therapy in patient 2 (likely milder phenotype). All GABA pathway metabolites (γ-hydroxybutyrate, glutamine, glutamate, total GABA, succinic semialdehyde) and TCA cycle metabolites (citrate, malate, fumarate, isocitrate, lactate) were significantly low in the homozygous knock-out aldh7a1 zebrafish compared to the wildtype zebrafish. Homozygous knock-out aldh7a1 zebrafish had decreased electron transport chain enzyme activities compared to wildtype zebrafish. Discussion We report impaired electron transport chain function, accumulation of glutamate in the central nervous system and TCA cycle dysfunction in human PDE-ALDH7A1 and abnormal GABA pathway, TCA cycle and electron transport chain in knock-out aldh7a1 zebrafish. Central nervous system glutamate toxicity and impaired energy production may play important roles in the disease neuropathogenesis and severity in human PDE-ALDH7A1.